088 Cohort of Clinical Practice Guidelines from the Spanish National Guideline Programme: A Survival Analysis. (15th August 2013) - García, L Martínez; Sanabria, A; David, R; Barajas, L; Fontecha, P Díaz del Campo; Sabadell, M Estrada; Ikobaltzeta, I Etxeandia; Álvarez, E García; González, A Louro; Fernandez, F Salcedo; Trujill, M; Alonso-Coello, P
Abstract : Background: Clinical Practice Guidelines (CPGs) recommendations need to be updated to maintain their validity. Objectives: To provide empirical estimates of the average time after which CPGs recommendations become obsolete. Methods: We developed a strategy to assess the validity of CPG recommendations, which included assessing their validity by surveying clinical experts, updating the literature search, screening references by pertinence and matching them with recommendations, and identifying pertinent, relevant and key references, and potential changes in each recommendation. A convenience sample of four CPGs was selected. We piloted our strategy in 20% of the recommendations from these CPGs (feasibility test) and we estimated our sample size. We performed a survival analysis and considered a CPG outdated when more than 20% of recommendations needed to be updated. Results: The four CPGs included 250 recommendations. A total of 39.133 (range 3.343–14.784) references were identified in the exhaustive literature search in a time frame of 3–5 years. The feasibility test identified 16 key references updating 8 recommendations. The number of recommendations required for the study was 113. A total of 674 references were marked as pertinent to these recommendations. Discussion: We developed a rigorous, replicable evaluation strategy to assess the validity of recommendations and estimate CPG obsolescence. Full final results will be present at the GIN meeting. Implications for Guideline Developers/Users: Our work is relevant for guideline developers because it provides information about the expected validity of CPGs recommendations.